STUDI LITERATUR: STRATEGI KOMUNIKASI PPID DALAM MENGATASI EQUAVOCALITY DI KEMENTRIAN KEUANGAN - Yuni Antika; Visye Antasya; Nira Sania Putri; Dhesta Adellya Santika; Nabila Trisya Fathiyah; Elivia Pasma Putri; Atrika Iriani (Jurnal Riset Multidisiplin Edukasi, 2026)
This study is motivated by the importance of effective public information management, which in practice is often confronted with issues of Equivocality or differences in the interpretation of information among individuals and work units within an organization. This study aims to examine the communication strategies of Information and Documentation Management Officers (PPIDs) as an effort to address Equivocality in organizational communication, particularly within the Ministry of Finance of the Republic of Indonesia. The method used in this study is a literature review, which involves identifying, selecting, and analyzing various relevant literature sources such as scientific journal articles, laws and regulations, and related policy documents. The findings indicate that Equivocality within the Ministry of Finance is influenced by four primary factors: the complexity of information classification regulations, disparities in employee competencies and tenure, a lack of systematic cross-unit coordination, and low information literacy among requesters. As a solution, the PPID implemented five key strategic dimensions, including strengthening internal coordination through intensive meetings, standardizing procedures through regulatory updates, enhancing human resource capacity, leveraging digital technology (such as e-PPID), and public education. In conclusion, through comprehensive communication strategies addressing both internal and external aspects, the Ministry of Finance’s PPID has proven capable of gradually reducing gaps in understanding and collectively managing shared meanings in the implementation of public information disclosure.